AB0512 Nasal Carriage of Staphylococcus Aureus in Patients with Systemic Lupus Erythematosus: Cause or Effect?. (10th June 2014) - Ceccarelli, F.; Iaiani, G.; Miranda, F.; Giordano, A.; Spinelli, F.R.; Perricone, C.; Truglia, S.; Alessandri, C.; Conti, F.; Valesini, G.
Abstract : Background: Staphylococcus aureus (SA) is a commensal bacterium which can be isolated mostly in the anterior nares. In immunosuppressive patients, SA could cause various infections, ranging from minor skin infections to severe pneumonia. Data from literature reported a prevalence of SA nasal carriage of about 25% in healthy subjects (HS). Patients affected by Wegener's granulomatosis and Rheumatoid Arthritis showed significantly higher rates of SA nasal colonisation compared with HS. In contrast, there are no studies concerning the patients with Lupus Erythematosus Systemic (SLE). Objectives: We aimed to analyse the prevalence of SA nasal carriers in a cohort of SLE patients. Secondly, we evaluated the correlations between the presence of nasal colonization and clinical, laboratory and therapeutical features. Methods: We enrolled 84 SLE patients (ACR criteria 1997, M/F 6/78; mean age 41.3±12.2 years, mean disease duration 141.5±102.6 months) and 154 HS blood donors, enrolled as control group. At each visit, SLE patients underwent a complete physical examination and the clinical/laboratory data were collected in a standardized, computerized, and electronically-filled form. The evaluation of serum complement C3 and C4 levels and determination of autoantibodies was obtained. Disease activity was assessed with the SLEDAI-2K. All the SLE patients and HS received a nasal swab in both anterior nares; the swabs were sent to microbiological laboratory for isolation and identification of SA. Results: SA nasal colonization prevalence was 23.8% in SLE patients and 28.6% in HS (P=NS). None of the detected SA were Methicillin-resistant. We analysed SLE patients according with the presence (N=20, group 1) or the absence (N=64, group 2) of the nasal colonization. Group 1 patients showed a significant higher frequency of renal involvement compared with group 2 (15.0% vs 3.1%; P=0.0009). Moreover, the presence of anti-dsDNA, RNP, SSA and SSB antibodies was significantly higher in group 1 (P<0.0001, P=0.03, P=0.005, P=0.03, respectively). Finally, although without reaching significant differences, group 1 patients showed higher mean values of SLEDAI-2K and flare number in the previous 12 months compared with group 2. Conclusions: In the present study we analysed the prevalence of SA nasal colonization in SLE patients, showing similar results in SLE patients and HS control group. Interestingly, in SLE patients the nasal colonization was associated with a more active disease, as demonstrated by higher values of disease activity indices, most frequent renal involvement and positivity for several autoantibodies. This association could be explained by two different hypothesis: first, the presence of SA nasal colonization could act as trigger for autoimmune process, perpetuating inflammatory condition. The second hypothesis suggests that the more active disease, requiring more aggressive immunosuppressant treatment, could facilitate the development of the nasal colonization. Further studies are needed to better clarify the relationship between SLE and SA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4226